2014
DOI: 10.4028/www.scientific.net/amr.922.264
|View full text |Cite
|
Sign up to set email alerts
|

Compression of Single-Crystal Micropillars of the Γ Intermetallic Phase in the Fe-Zn System

Abstract: The deformation behavior of the Γ (gamma) phase in the Fe-Zn system has been investigated via room-temperature compression tests of single-crystal micropillar specimens fabricated by the focused ion beam method. Trace analysis of slip lines indicates that {110} slip occurs for the specimens investigated in the present study. Although the slip direction has not been uniquely determined, the slip direction might be <111> in consideration of the crystal structure of the Γ phase (bcc).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…We have also found that micropillars of the ζ, δ 1k and δ 1p phases exhibit plasticity in compression in the single-crystal form. [30][31][32] In addition to the compression deformability, however, the fracture toughness of each of the intermetallic compounds is essential to improve the understanding of the coating failure in GA steels. In the present study, therefore, we measure the fracture toughness values of each of the compounds by bend testing of chevron-notched single-crystal cantilever microbeams, 33) which are FIB-machined from polycrystals with a relatively large grain size.…”
Section: Fracture Toughness Of the Fe-zn Intermetallic Compounds Measmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also found that micropillars of the ζ, δ 1k and δ 1p phases exhibit plasticity in compression in the single-crystal form. [30][31][32] In addition to the compression deformability, however, the fracture toughness of each of the intermetallic compounds is essential to improve the understanding of the coating failure in GA steels. In the present study, therefore, we measure the fracture toughness values of each of the compounds by bend testing of chevron-notched single-crystal cantilever microbeams, 33) which are FIB-machined from polycrystals with a relatively large grain size.…”
Section: Fracture Toughness Of the Fe-zn Intermetallic Compounds Measmentioning
confidence: 99%
“…This is consistent with our recent results of single-crystal micropillar compression for the Γ, δ 1k , δ 1p and ζ phases that the CRSS value almost monotonically increases with increasing Fe content (δ 1k and δ 1p were pre-strained by Vickers indentation before the FIB-machining of the micropillars). [30][31][32] 4.2.2. Composition Dependence within the Γ-phase Solid Solubility Range The Γ phase possesses a relatively wide solid solubility range (22 − 32 at.%Fe).…”
Section: Composition Dependence Over the Five Intermetallic Compoundsmentioning
confidence: 99%
“…In this perspective, the crystal structure information for these intermetallics is fundamentally very important to consider elementary processes of plastic deformation such as slip planes, slip directions, dislocation Burgers vectors and dislocation dissociation. 18,19,24,25) The crystal structures of all the Fe-Zn intermetallics, except for that of the δ 1k phase, have long been investigated by X-ray diffraction in the past. [26][27][28][29][30][31][32][33][34] In general, all of them have a very complex crystal structures comprising coordinated polyhedra such as icosahedra.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, however, a method based on compression testing of small pillars of single crystals of the order of micrometer size, which can be prepared from relatively small crystal grains in polycrystals by focused ion beam (FIB) machining, has been developed and opened a way to measure CRSS values of alloys even if large single crystals are unavailable [12][13][14][15][16]. It has been known that the CRSS values of single-crystal micropillars in fcc and body-centered cubic (bcc) metals decrease with the increase in pillar size, obeying an inverse power-law scaling [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Since the occurrence of yield stress anomaly in the constituent γ′ phase is important for the strength of γ + γ′ two-phase alloys at high temperatures, comparison of the strength of Co 3 (Al,W) with those with Ni 3 Al-based L1 2 compounds should be made to see how significantly Co 3 (Al,W) contributes to the strength of Co-based superalloys especially at high temperatures. However, the critical resolved shear stress (CRSS) has not been available for Co 3 (Al,W) due to the difficulties in preparing single crystals of the γ′-Co 3 (Al,W) single-phase large enough for the study of plastic deformation [11].In recent years, however, a method based on compression testing of small pillars of single crystals of the order of micrometer size, which can be prepared from relatively small crystal grains in polycrystals by focused ion beam (FIB) machining, has been developed and opened a way to measure CRSS values of alloys even if large single crystals are unavailable [12][13][14][15][16]. It has been known that the CRSS values of single-crystal micropillars in fcc and body-centered cubic (bcc) metals decrease with the increase in pillar size, obeying an inverse power-law scaling [17][18][19][20].…”
mentioning
confidence: 99%